Communication Strategies in Addressing Open Defecation Challenges: A Survey of La Dade-Kotopon Municipality - Owusu, Selorm Kakraba (UniMAC-GIJ, 2021)
Strategies used by the local authorities to fight open defecation in the communities are either not enough or not effective enough; as the government seems to be taking up the fight against open defecation. Studies in other jurisdictions have shown that that communication can be used to solve the problem. The main objective of the study was to assess the effectiveness of communication strategies employed by the local to fight open defecation in Ghana. The study employed a qualitative approach using data gathered through open ended questionnaires (interview guide) from 10 community members in various capacities including municipal officers, opinion leaders, beach workers, and household heads. The data was analysed by thematic analyses. The study found that communication and education has been the main means of the fight against open defecation in the La community. This has largely been done through public communication vans. The study also revealed this communication strategy has not been effective, since the practice of open defecation is still going on. The respondents revealed that this communication strategy has failed because of culture and refusal to change behavioural practices; funding to sustain communication, lack of toilets in public and households; illiteracy; and population growth. The participants recommended that for communication to be effective, there must be more and appropriate communication channels emphasising the risks associated with the practice of open defecation and funding to ensure sustainability.
Thesis
Keywords: Communication, Strategies, Open Defecation Challenges, La Dade-Kotopon Municipality, Accra, Ghana